Biology of Hestiasula brunneriana Saussure (Dictyoptera: Mantidae) - Ahmad, Mukhtar; Vijayachandran, S. N.; Basu Choudhuri, J. C. (Indian Forester, 1985)
Hestiasula brunneriana Sausure (Dictyoptera : Mantidae) is a sylvan species of mantid which prey on immature stages and adults of teak defoliators and several other forest pests. Biology and behaviour of the species were studied under laboratory conditions. Fecundity of the female and the longevity of males and females were also studied.